Association between bacterial vaginosis and Herpes simplex virus type-2 infection: implications for HIV acquisition studies. Issue 5 (10th May 2007) - Nagot, Nicolas; Ouedraogo, Abdoulaye; Defer, Marie-Christine; Vallo, Roselyne; Mayaud, Philippe; Van de Perre, Philippe
Abstract : Objectives: Bacterial vaginosis (BV) and Herpes simplex virus type-2 (HSV-2) have been linked to an increased risk of HIV-1 acquisition. Recent research suggests an association between BV and HSV-2 acquisition, but the converse has not been studied. Here, we investigate whether an association exists between BV and HSV-2 infection Methods: We examined the determinants of BV occurrence in a cohort of female sex workers in Burkina Faso. Participants were followed every 3 months for diagnosis of genital infections and report of sexual behaviours. Factors associated with BV occurrence were assessed using generalised estimating equation models. Results: We enrolled 273 women (mean age, 28 years) and conducted 812 follow-up visits (mean 2.93 visit per woman). Baseline seroprevalence of HIV-1, HSV-2 and recent syphilis were 31.5%, 70.1% and 0.4%, respectively, while baseline prevalence of BV, Trichomonas vaginalis (TV) and Candida albicans were 20.5%, 3.3% and 2.5%, respectively. In multivariable analysis, HSV-2 (relative risk (RR) = 1.73, 95% CI 1.12 to 2.65), HIV-1 (RR = 1.76, 95% CI 1.30 to 2.40), TV (RR = 1.5, 95% CI 1.0 to 2.3), and having ⩾3 sexual partners in the preceding week (RR = 2.2, 95% CI 1.1 to 4.6) were independently associated with BV, while hormonal contraception showed a protective effect (RR = 0.11, 95% CI 0.02 to 0.70). Conclusions: HSV-2 infection was associated with BV occurrence in this population. As HSV-2 is strongly linked to HIV-1 acquisition, studies assessing the cofactor effect of BV on HIV acquisition should control for the presence of HSV-2. Further studies are required to investigate the relative effect of asymptomatic HSV-2 shedding and/or genital ulcerations on BV occurrence.